Understanding Second-Year Students’ Speaking Anxiety in EFL Virtual Classroom - Nurjihan, Ariqoh; Firmansyah, Fancista Azriel; Shofia, Afrina Majdanis; Rohmana, Wahyu Indah Mala (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2026)
This study investigates speaking anxiety among second-year EFL students in online learning contexts by analyzing four main dimensions: their emotional responses, the factors that provoke anxiety, its impact on speaking performance, and the strategies they use to manage it. Using a qualitative descriptive design, the study gathers data through interviews with fifteen students who have previously engaged in online English-speaking activities. The results show that the experience of speaking anxiety differs across individuals. While some students feel more comfortable in virtual classes because the lack of direct eye contact helps reduce pressure, others report heightened anxiety due to insufficient preparation, poor internet connectivity, limited vocabulary, or fear of errors and negative judgment. These influences shape students’ fluency and concentration during speaking tasks. To deal with anxiety, students employ various strategies, such as preparing their material beforehand, calming themselves before speaking, using humour to ease tension, or utilizing supporting tools like digital prompters. The lecturer’s behaviour also plays a crucial role, as supportive and expressive instructors tend to create a more relaxed atmosphere, whereas less engaging teaching styles can intensify stress. Online learning environments may either lessen or heighten anxiety depending on classroom management and learners’ readiness. Therefore, teachers are encouraged to foster a supportive and comfortable learning space to enhance students’ confidence in speaking.